Effect of powder flowrate on the microstructure of FeCrV15 clad, developed via the laser cladding technique. (2022) - Aramide, Basiru; Sadiku, Rotimi; Popoola, Patricia; Pityana, Sisa; Jamiru, Tamber
Abstract: Steel utilized in mining and tillage devices is highly susceptible to wear and corrosion attacks due to its poor tribological property when presented to unfavorable working conditions common to mining and tillage activities. This leads to an intensified research activity to improve its properties. The blend of chromium carbide and vanadium carbide (VC) reinforcement in iron-based hard-facings has dramatically improved the wear and corrosion resistance of the devices subjected to adverse abrasive and impact conditions. This comparative study deposited high carbon ferrochrome FeCrV15 coating on steel baseplates to form Cr-rich carbide and vanadium carbide in-situ at two different powder flow rates: 5 g/min and 6 g/min. The effect of the powder flow rate on the morphology of the precipitated carbide, the hardness of the coatings, and the specific laser beam power of the individual grain of powder was examined and compared.